2015
DOI: 10.1111/dth.12229
|View full text |Cite
|
Sign up to set email alerts
|

The topical treatment of anthroponotic cutaneous leishmaniasis with the tincture of thioxolone plus benzoxonium chloride (Thio-Ben) along with cryotherapy: a single-blind randomized clinical trial

Abstract: A simple efficacious topical treatment for cutaneous leishmaniasis (CL) is still an unresolved challenge. This study aimed to evaluate the efficacy of the topical use of thioxolone plus benzoxonium chloride (Thio-Ben) tincture in combination with cryotherapy in comparison with intralesional meglumine antimoniate (Glucantime) along with cryotherapy in treating anthroponotic CL (ACL). The study was conducted in Leishmaniasis Center in Dadbin Health Care Clinic, Kerman, Iran. Sixty-four CL lesions were randomly a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…2009 , El-Sayed & Anwar 2010 , Kashani et al 2010 , Van Thiel et al 2010 , Meymandi et al 2011 , Safi et al. 2012 , Bumb et al 2013 , Khatami et al 2013 , Mohammedzadh et al 2013 , Soto et al 2013 , Dieterle & Pillekamp 2014 , Stahl et al 2014 , Banihashemi et al 2015 , Parizi et al 2015 , Ranawaka et al. 2015 ) clinical trials addressing intralesional therapy over the last 10 years were identified.…”
Section: Resultsmentioning
confidence: 99%
“…2009 , El-Sayed & Anwar 2010 , Kashani et al 2010 , Van Thiel et al 2010 , Meymandi et al 2011 , Safi et al. 2012 , Bumb et al 2013 , Khatami et al 2013 , Mohammedzadh et al 2013 , Soto et al 2013 , Dieterle & Pillekamp 2014 , Stahl et al 2014 , Banihashemi et al 2015 , Parizi et al 2015 , Ranawaka et al. 2015 ) clinical trials addressing intralesional therapy over the last 10 years were identified.…”
Section: Resultsmentioning
confidence: 99%
“…Sex was considered an inclusion criterion in 94.3% ( n = 100) of studies enrolling 11 081 patients; 87.7% ( n = 93) enrolled participants of both sexes , seven studies (6.6%) enrolled only men ; in five studies (4.7%), although sex was not specified in the inclusion criteria, inclusions can be derived from the results , and one study did not refer to the sex of the participants (Table ). For pregnancy and lactation, see Exclusion criteria below (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…Type of lesions was considered in 13.2% ( n = 14) of studies; all included ulcerated lesions, but while nine (64.3%) also allowed all other types of lesions, five (35.7%) restricted inclusions to ulcers. Of note, one study limited enrolment to ulcerated lesions for only one of the two topical treatment groups (local application of liquid solution composed of thioxolone and 3 mg benzoxonium chloride + cryotherapy) (Table ) .…”
Section: Resultsmentioning
confidence: 99%
“…Niosomes have potential as new and selective drugs for treating important diseases, including leishmaniasis (Kazi et al 2010). Previous studies have evaluated the anti-leishmanial effects of Thio-Ben on patients (Daie Parizi et al 2015) and in the present work, we evaluated the in vitro leishmanicidal effects of benzoxonium chloride (one of the components of Thio-Ben) and its niosomal forms against different forms of the parasite ( L. tropica ).…”
Section: Discussionmentioning
confidence: 99%
“…However, studies have suggested that benzoxonium chloride inhibits certain bacterial enzymes ([CSL STYLE ERROR: reference with no printed form.]). In 2015, Thio-Ben was tested in a clinical trial and it evaluated the efficacy of the topical use of tioxolone plus benzoxonium chloride (Thio-Ben) tincture in combination with cryotherapy as compared to intralesional meglumine antimoniate (glucantime™) along with cryotherapy in treating anthroponotic CL (ACL) (Daie Parizi et al 2015). The study reported that the topical use of Thio-Ben combined with cryotherapy showed good efficacy in treating ACL along with benefits pertaining to more patient compliance and less side effects than intralesional glucantime (Daie Parizi et al 2015).…”
Section: Introductionmentioning
confidence: 99%